Examining Oxygen Saturation and Peak Volume Correlation in Respiratory Disorders: A Study at PCM/PCA Ciledug - Fitriana, Rizni; Irena Ujianti; Teguh Haryo Sasongko; Yashiro, Takashi (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2023)
This cross-sectional study sought to determine the correlation between oxygen saturation and peak flow meter readings, taking into account hemoglobin levels. Participants aged 55 years and over were examined using direct measurement methods, with hemoglobin measured via the strip test method, and oxygen saturation and peak flow meter values assessed using a pulse oximeter and peak flow meter, respectively. Analysis of the collected data from 12 subjects, averaged 63 years old, revealed a significant correlation between oxygen saturation (average 96.6%) and peak flow volume (average 223.3 mL/mnt) (r=0.727, p=0.007). The findings suggest that this relationship is more potent in individuals with respiratory disorders or under certain environmental risk factors. Nonetheless, in healthier contexts, the correlation may be weaker or absent, emphasizing the need for further research to enhance the management of respiratory and lung disorders